Extensometric measurements in Hungary - MENTES, Gyula; ÚJVÁRI, Gábor (Contributions to Geophysics and Geodesy, 2021)
From the beginning of the eighties till 2000 four extensometric stations were established in Hungary for observing Earth tide deformations and recent tectonic movements. This paper presents these observatories and deals in detail with the results of measurements concerning the determination of tidal parameters and gives the rates of the tectonic movements in the Pannonian Basin on the basis of the latest measurements.